Study of Optimization of Power Consumption and Layout Size Is Particularly Critical For the Amplifier Circuit (International Journal of Scientific Research in Science and Technology, 2025)
In this paper, we present the optimization of power consumption and layout size, particularly critical for the amplifier circuit.